2015
DOI: 10.1039/c5py00660k
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally benign synthesis of saturated and unsaturated aliphatic polyesters via enzymatic polymerization of biobased monomers derived from renewable resources

Abstract: Biobased saturated aliphatic polyesters and photo-curable unsaturated aliphatic polyesters are enzymatically polymerized, and their structure–property relationships are systematically studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 60 publications
(112 reference statements)
5
70
0
Order By: Relevance
“…The superior control over branching degree while effectively avoiding cross‐linking in obtaining multifunctional polyol‐polyesters has made lipase a promising nontoxic method for branching controlled preparation of hyperbranched polyesters. As it is only performed on ester bonds, many sensitive groups (SH, SS, N 3 , CH  CH 2 , et al) can be preserved during polymerization . At present, glycerol and many other sugars like D‐sorbitol, D‐mannitol, and lactose have been polymerized with diacids/diesters, especially with divinyl esters in polar solvent(e.g., tetrahydrofuran or acetonitrile), which is preferred in achieving high molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…The superior control over branching degree while effectively avoiding cross‐linking in obtaining multifunctional polyol‐polyesters has made lipase a promising nontoxic method for branching controlled preparation of hyperbranched polyesters. As it is only performed on ester bonds, many sensitive groups (SH, SS, N 3 , CH  CH 2 , et al) can be preserved during polymerization . At present, glycerol and many other sugars like D‐sorbitol, D‐mannitol, and lactose have been polymerized with diacids/diesters, especially with divinyl esters in polar solvent(e.g., tetrahydrofuran or acetonitrile), which is preferred in achieving high molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] This is mainly due to the high melting temperatures (T m ) and low solubility of polyamides. 33 In our laboratory the hydrolase-catalyzed polymerization is actively investigated and therefore various polyesters and polyamides are successfully produced via enzymatic polymerization, e.g., saturated and unsaturated aliphatic polyesters, [38][39][40] glucose-based polyesters, 41 furan-based polyesters, 42,43 semi-aromatic oligoamides, 44 oligo(amino acid)s, 45 aliphatic polyamides [46][47][48] and poly(amide-co-ester)s. 49 The previous studies reported by our laboratory revealed that Novozym 435 (N435), which is an immobilized form of Candida antarctica Lipase B (CALB) on acrylic resin, is a robust biocatalyst for polyester and polyamide synthesis; and N435 works well with FDCA derivatives in biocatalytic polyester synthesis. 42,43 Based on these results, we are confident that N435 is also capable of catalyzing the polymerization of FDCA derivatives and aliphatic diamines.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers offer a promising alternative to non‐degradable plastics due to their inherent tendency to undergo degradation under ambient conditions . Aliphatic polyesters are one of the major categories of biodegradable polymers and their popularity in biomedical applications is driven by their biocompatible nature and good mechanical properties . Most of these polymers are derived from renewable resources such as cellulose and starch and hence they can serve as a solution to the shortages arising from finite petroleum resources .…”
Section: Introductionmentioning
confidence: 99%